1988
DOI: 10.1007/bf00008129
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic carbon fluctuations in Dal Lake waters

Abstract: Dissolved organic carbon (DOC) fluctuations were studied in the surface water of Dal Lake from May 1984 to April 1985, at monthly intervals. Concentration of DOC varied from 0.140 mg 1 -' to 0.725 mg 1 -'. A minimum was recorded in May and September, while an increase was observed during December and January. The fluctuations during the observation period showed a relationship with temperature and pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Pesticides contained in sediments may effect the ecosystem, particularly the benthic community, to a greater extent than those dissolved in water. Several authors have studied the physico‐chemical characters of various lakes in India 8–10. However, a detailed survey of the literature indicated that there was no comprehensive study to provide information about pesticide content in sediments from Kolleru Lake, although pesticides were extensively used in the catchment area of the lake.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides contained in sediments may effect the ecosystem, particularly the benthic community, to a greater extent than those dissolved in water. Several authors have studied the physico‐chemical characters of various lakes in India 8–10. However, a detailed survey of the literature indicated that there was no comprehensive study to provide information about pesticide content in sediments from Kolleru Lake, although pesticides were extensively used in the catchment area of the lake.…”
Section: Introductionmentioning
confidence: 99%